2020
DOI: 10.1002/rmv.2164
|View full text |Cite
|
Sign up to set email alerts
|

A review on disease burden and epidemiology of childhood parainfluenza virus infections in Asian countries

Abstract: Summary Human parainfluenza viruses (HPIVs) are an important cause of acute respiratory tract infections (ARTIs) in children less than 5 years, second only to human respiratory syncytial viruses (HRSVs). Generally, patients infected with HPIVs are treated in outpatient clinics, yet also contribute to ARTI‐associated hospitalization in children. Although HPIV infections are well studied in developed countries, these infections remain under‐investigated and not considered in the routine laboratory diagnosis of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 75 publications
2
10
0
Order By: Relevance
“…Variously, in other Asian countries such as Bangladesh, the prevalence of HPIV-3 was reported to be 10.5% among children between August 2014 and July 2015 [ 25 ]. In addition, a recent study reported that the prevalence of HPIV in children under 5 years of age in most Middle-East countries was more than 15%, but did not specifically report the prevalence of HPIV-3 [ 26 ]. In the present study, the RSV seasonal distribution is defined by the fall and winter peaks.…”
Section: Discussionmentioning
confidence: 99%
“…Variously, in other Asian countries such as Bangladesh, the prevalence of HPIV-3 was reported to be 10.5% among children between August 2014 and July 2015 [ 25 ]. In addition, a recent study reported that the prevalence of HPIV in children under 5 years of age in most Middle-East countries was more than 15%, but did not specifically report the prevalence of HPIV-3 [ 26 ]. In the present study, the RSV seasonal distribution is defined by the fall and winter peaks.…”
Section: Discussionmentioning
confidence: 99%
“…Not much could be found in the literature about the global burden estimates for the parainfluenza virus. Literature from Asia reported a variable prevalence of HPIV ranging from 1 to 66%, with 6.95% as the Indian average prevalence ( Rafeek et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…These changes resulted in an unprecedented increase in the detection rate of hPIV, especially in the young age groups, in September 2021 in the Republic of Korea. Among the enveloped viruses, hPIV is the most common pathogen causing common cold in infants [18,19]. Most children over 5 years of age possess antibodies against hPIV3 [20,21]; however, infants are vulnerable to hPIV3 infection [22,23].…”
Section: Discussionmentioning
confidence: 99%